Investigating the effect of toothed edges and large openings on the seismic behavior of confined masonry walls - Tan, Amber Chun En (2017)
Confined masonry structures are commonly seen in seismically active regions in developing countries, due to their satisfactory performances in past earthquakes, cost effectiveness and ease of construction. However, confined masonry construction is a less researched field compared to other techniques which are more commonly used in urban areas, such as reinforced concrete construction. As a result, relevant codes are less extensive, and best-practices that builders rely on can be ambiguous or contradictory.